Diagnosis of rotavirus infections and their reporting in the Czech Republic in 2001 - Pazdiora, P (Epidemiologie, mikrobiologie, imunologie, 2003)
In 2001 in 44 laboratories in the CR by laboratory methods 2,250 rotavirus infections were confirmed. From the total number of diagnostic departments 37, i.e. 84.1% use latex agglutination. Among the examined subjects children under 3 years predominated a positive finding being confirmed in 23.0%. The specific morbidity in this age group was 651.3 cases/100,000/year. The hygiene service received in the course of the year 851 notifications of sporadic cases and 72 infections which developed in three epidemics. As to infections confirmed by laboratory examinations only 39.3% were notified. Probably also one imported case of the disease was recorded, no death was reported.